Spray coating process of MWCNT/epoxy nanocomposite films for aerospace applications: Effects of process parameters on surface electrical properties. (June 2019) - Laurenzi, Susanna; Clausi, Marialaura; Zaccardi, Federica; Curt, Ugo; Santonicola, M. Gabriella
Abstract: Nanocomposite coatings on flexible membranes possess many interesting properties useful in aerospace applications, such as thermal blankets and charging mitigation layers. However, their fabrication is not trivial and the overall performance is strongly dependent on the manufacturing process, since it influences the filler distribution and so the homogeneity of the coated film. In this work, carbon nanotube/epoxy nanocomposite films were deposited on Mylar substrates by spray coating process. The effects of the process parameters on the morphology and on the electrical properties of the nanocomposite films were investigated. In particular, the influence of the nozzle diameters and the distance between the nozzle and the target substrate, as well as the concentration of the multiwalled carbon nanotubes (MWCNT) were studied. The electrical properties of the MWCNT/epoxy nanocomposite surfaces were determined using impedance spectroscopy in the frequency range from 20 Hz to 2 MHz. The analysis was performed on samples extracted from different regions of the nanocomposite films, in order to assess their property homogeneity. Highlights: CNT/epoxy nanocomposite films were fabricated on Mylar by spray coating process. Spraying parameters influence the electrical properties of the nanocomposite films. High concentrations of MWCNTs strongly limit the use of the spray coating process. Uniform surface conductivity is achieved with larger nozzle and concentration of 1 wt% of MWCNT. Variation of surface conductivity with the frequency depends on MWCNT loading.